Secondary metabolites with antimicrobial activity produced by thermophilic bacteria from a high-altitude hydrothermal system - Pardo-Esté, Coral; Cortés, Johanna; Castro-Severyn, Juan; Pérez, Vilma; Henriquez-Aedo, Karem; Cuadros, Fabian; Yañez, Carolina; Cuadros-Orellana, Sara; Dorador, Cristina; Molina, Veronica; Eissler, Yoanna; Paquis, Pablo; et al. (Frontiers in Microbiology, 2024)
Thermophilic microorganisms possess several adaptations to thrive in high temperature, which is reflected as biosynthesis of proteins and thermostable molecules, isolation and culture represent a great methodological challenge, therefore High throughput sequencing enables screening of the whole bacterial genome for functional potential, providing rapid and cost-effective information to guide targeted cultures for the identification and characterization of novel natural products. In this study, we isolated two thermophilic bacterial strains corresponding to Bacillus LB7 and Streptomyces LB8, from the microbial mats in the Atacama Desert. By combining genome mining, targeted cultures and biochemical characterization, we aimed to identify their capacity to synthesize bioactive compounds with antimicrobial properties. Additionally, we determined the capability to produce bioactive compounds under controlled in vitro assays and detected by determining their masses by Thin-Layer Chromatography/Mass Spectrometry (TLC/MS). Overall, both isolates can produce antimicrobial (e.g., Myxalamide C by-product) and antioxidants (e.g. Dihydroxymandelic Acid, Amide biotine and Flavone by-products) compounds. Bacillus LB7 strain possesses a more diverse repertoire with 51.95% of total metabolites unmatched, while Streptomyces LB8 favors mainly antioxidants, but has over 70% of unclassified compounds, highlighting the necessity to study and elucidate the structure of novel compounds. Based on these results, we postulate that the uncultured or rare cultured thermophiles inhabiting high-altitude hydrothermal ecosystems in the Atacama Desert offer a promising opportunity to the study of novel microbial bioactive compounds.